2012
DOI: 10.1111/j.1399-3062.2012.00744.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial urinary tract infection after solid organ transplantation in the RESITRA cohort

Abstract: Background Urinary tract infection (UTI) is the most common infection in renal transplant patients, but it is necessary to determine the risk factors for bacterial UTI in recipients of other solid organ transplants (SOTs), as well as changes in etiology, clinical presentation, and prognosis. Methods In total, 4388 SOT recipients were monitored in 16 transplant centers belonging to the Spanish Network for Research on Infection in Transplantation (RESITRA). The frequency and characteristics of bacterial UTI in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
124
2
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(146 citation statements)
references
References 37 publications
10
124
2
10
Order By: Relevance
“…Vidal et al (16) reported E. coli extended spectrum beta-lactamase (ESBL) producers in 26.3% of their samples. In addition, quinolone resistance was identifi ed in 38% of E. coli isolates, 31% of Klebsiella spp.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vidal et al (16) reported E. coli extended spectrum beta-lactamase (ESBL) producers in 26.3% of their samples. In addition, quinolone resistance was identifi ed in 38% of E. coli isolates, 31% of Klebsiella spp.…”
Section: Methodsmentioning
confidence: 99%
“…In one prospective cohort multicenter study that enrolled 2,052 renal transplant patients, the incidence of UTIs was 10.04%, and the independent risk factors were age, female sex and the need for dialysis post-transplantation (16) . Another report with 393 renal transplanted patients showed a UTI incidence of 56.23%, and the only associated risk factor was age (5) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, randomized controlled trials to assess the efficacy of therapy for asymptomatic bacteriuria to improve long-term kidney function are currently lacking. This is particularly relevant, given the widespread emergence of extended-spectrum betalactamase-and carbapenemaseproducing Enterobacteriaceae strains, which have been identified as a major concern in the field of transplant infectious diseases (170,171). In kidney recipients, a risk factor for recurrent UTI after transplantation is the acquisition of MDR pathogens during hospital admission; unfortunately, few antibiotics are available to treat recurrent UTI caused by MDR pathogens (181).…”
Section: Clinical Datamentioning
confidence: 99%
“…The main risk factors for UTI are age, female sex, and the need for immediate posttransplant dialysis (171).…”
Section: Bacterial Respiratory Tract Infectionmentioning
confidence: 99%